2016
DOI: 10.1007/s13277-016-4985-2
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid may exerts its cytotoxic effect through rassf1a expression induction in acute myeloid leukemia

Abstract: In acute myeloid leukemia (AML), despite the acceptance of standard intensive chemotherapy as an optimal induction regimen for all age groups, in the elderly patients, the best treatment should meet the challenge of multiple factors like age, comorbidities, and cytogenetics, making them ineligible for standard induction chemotherapy. Using the current low-intensity therapies like decitabine, azacitidine, and low-dose cytarabine as a single arm, outcomes for these patients remain poor. As a histone deacetylase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…To date, the different mechanisms of HDACis combined with chemotherapeutic agents such as topoisomerase inhibitors, platinumbased chemotherapeutics, proteasome inhibitors, tyrosine kinase pathway inhibitors and epigenetic modifiers for advanced or drug-resistant hematological malignancies include (1) acetylating histones and inducing p21-CDK-mediated cell cycle arrest; (2) inducing apoptosis by regulating the expression of pro-and antiapoptotic genes through the intrinsic or extrinsic pathway; (3) inducing DNA damage and oxidative stress; (4) activating BTK (in CLL) or inhibiting ERK (in MM) and AKT (in CML) signaling pathways; and (5) regulating the expression of drug resistance-related molecules, such as downregulating BCR-ABL and upregulating Bim in hematological malignancies and downregulating CD44 in multiple myeloma (MM), NF-κB in ALL, γ-catenin in CML, and BRCA1, CHK1 and RAD51 in AML [126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145]. Specific combination strategies and their corresponding mechanisms are summarized in Table 3 [146][147][148][149][150][151][152][153][154][155]. Moreover, two-phase I clinical trials were carried out to assess the DNA methyltransferase (5-azacitidine) and HDACi (phenylbutyrate) for the treatment of hematological malignancies.…”
Section: The Application Of Hdacis In Malignant Hematopoiesismentioning
confidence: 99%
“…To date, the different mechanisms of HDACis combined with chemotherapeutic agents such as topoisomerase inhibitors, platinumbased chemotherapeutics, proteasome inhibitors, tyrosine kinase pathway inhibitors and epigenetic modifiers for advanced or drug-resistant hematological malignancies include (1) acetylating histones and inducing p21-CDK-mediated cell cycle arrest; (2) inducing apoptosis by regulating the expression of pro-and antiapoptotic genes through the intrinsic or extrinsic pathway; (3) inducing DNA damage and oxidative stress; (4) activating BTK (in CLL) or inhibiting ERK (in MM) and AKT (in CML) signaling pathways; and (5) regulating the expression of drug resistance-related molecules, such as downregulating BCR-ABL and upregulating Bim in hematological malignancies and downregulating CD44 in multiple myeloma (MM), NF-κB in ALL, γ-catenin in CML, and BRCA1, CHK1 and RAD51 in AML [126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145]. Specific combination strategies and their corresponding mechanisms are summarized in Table 3 [146][147][148][149][150][151][152][153][154][155]. Moreover, two-phase I clinical trials were carried out to assess the DNA methyltransferase (5-azacitidine) and HDACi (phenylbutyrate) for the treatment of hematological malignancies.…”
Section: The Application Of Hdacis In Malignant Hematopoiesismentioning
confidence: 99%
“…The significance of the Hippo-YAP1 signaling pathway has recently been identified in myeloma cells [2123]. However, the contribution of Hippo signaling to the pathophysiology of AML remains unclear although a few reports mentioned Hippo signaling in AML cells [21, 24]. Regarding MSCs in patients with AML, it has been demonstrated that deregulation of proteoglycans, adhesion molecules, expression of cytokines, metabolic and endocytosis pathways could be detected by whole-exome sequencing [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, additional mechanisms may contribute to the antiproliferative and proapoptotic effects of valproic acid. First, the hippo signaling pathway is important for regulation of proliferation and apoptosis, and altered signaling through this pathway (possibly due to the induction of RASSF1A expression) may be an antileukemic mechanism especially in patients with normal and adverse karyotype [ 23 ]. Second, valproic acid in combination with interferon (IFN)-α alters the activation/phosphorylation of Akt, ERK1/2, p38, and p53 [ 24 ].…”
Section: Experimental and Clinical Studies Of Valproic Acid In Non-apl Variants Of Amlmentioning
confidence: 99%